2012
DOI: 10.12806/v11/i1/rf2
|View full text |Cite
|
Sign up to set email alerts
|

The Durable Effects of Short-Term Programs on Student Leadership Development

Abstract: Research involving students (N=612) at a large, research-extensive university who participated in voluntary short-term leadership programs showed an increase in leadership capacity, even when measured three months later. A popular assessment tool, the Socially Responsible Leadership Scale (SRLS), was used. Not all leadership competency scores showed significant increase after training, which may indicate that some leadership capacities may be more amenable than others to development through short-term programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 31 publications
4
38
0
Order By: Relevance
“…Additionally, a few program evaluation studies also reported the effectiveness of leadership education programs. For example, based on the social change model, Rosch and Caza (2012) found that students showed greater leadership capacities in the commitment to serving the collectives, working with a common purpose, handling controversy with civility, and citizenship after joining the voluntary short-term leadership programs.…”
Section: Leadership Programs In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a few program evaluation studies also reported the effectiveness of leadership education programs. For example, based on the social change model, Rosch and Caza (2012) found that students showed greater leadership capacities in the commitment to serving the collectives, working with a common purpose, handling controversy with civility, and citizenship after joining the voluntary short-term leadership programs.…”
Section: Leadership Programs In Higher Educationmentioning
confidence: 99%
“…However, few studies are able to inform the causal relationship between leadership program and students' developmental outcomes. Previous studies often used the correlational design (e.g., Dugan and Komives 2010), the pretest-posttest design without a control group (e.g., Rosch and Caza 2012) or the posttest-only design (e.g., Black and Earnest 2009), while these research designs are low in internal validity. In other words, it is still not clear whether participation in leadership programs leads to students' improvement in leadership capacities.…”
Section: Research Gapsmentioning
confidence: 99%
“…This paradigm shift manifests itself also in leader requirements: today's leadership theory has departed from the industrial foci on hierarchy, control and division of labour and moved to a post-industrial accent on relationships, networks, trust, ethics and participation [54]. This also reflects a shift in research emphases: where leadership was earlier the subject of psychology studies, it is presently examined through the lens of social psychology, interested in the role of the individual as a group member in a social setup [55].…”
Section: Categories Of Leader Competencesmentioning
confidence: 99%
“…34 However, the literature includes studies demonstrating higher levels of leadership skills following structured leadership programming. 35 In particular, one study indicates that participation in an undergraduate elective training program had a positive impact on Socially Responsible Leadership Scale scores and that the effects persisted 3 months after program completion. 35 …”
Section: Motivation For Teaching and Learningmentioning
confidence: 99%
“…35 In particular, one study indicates that participation in an undergraduate elective training program had a positive impact on Socially Responsible Leadership Scale scores and that the effects persisted 3 months after program completion. 35 …”
Section: Motivation For Teaching and Learningmentioning
confidence: 99%